GEL BAIT FOR GERMAN COCKROACH, Blattella germanica (DICTYOPTERA : BLATTELLIDAE) CONTROL : LABORATORY AND FIELD STUDIES - Suliyat
German cockroach (Blatella germanica) is found in various household, hotel, and restaurant. It is an important pest in aesthetics, economical and medical aspect. This cockroach is widespread species. It is found in almost every part of the world. It is mostly controlled by insecticide. However, intensive insecticide application caused environmental and resistance problems. In the last few years, Insecticide formula of bait is mostly used to control German cockroach in developed countries, but in Indonesia, it has been used limitedly. Bait has low impact, safety and could easily be used. This study was carried out to evaluate efficacy of bait on B. germanica in the laboratory and the field. The bait formulation consisted of attractant and active ingredient of fipronil insecticide 0.03%. Four bait formulations was made with different attractant namely chicken liver, banana–honey, cow blood and cockroach fecal. The result of the laboratory test showed that the time needed for 100% cockroach of mortality was 36, 48, 60, and 72 hours for chicken liver, banana-honey, cow blood, and fecal cockroach, respectively. Statistical analysis (Anova and Duncan test) showed that baiting formula of banana-honey and chicken liver were not significantly different (p ? 0.05). Considering the textural consistency of baiting in a longer time, baiting formula which consisted of banana-honey was chosen for further study. This next study was conducted to evaluate the efficacy of banana-honey bait in field to control B. germanica. Field test was carried out in 18 restaurant kitchens in Bandung. The total population before treatment was estimated with visual and sticky trap sampling methods. Visual method showed that total counting was higher than that of sticky trap method. Then visual method was used to monitor B. germanica population after treatment. Sanitation evaluation was conducted to determine sanitation level from 1 – 5 levels (clean – severely dirty). The result of sanitation evaluation showed that the poorer sanitation the more high population of B. germanica (Person correlation analysis, 0.9). The result of gel bait in the kitchen showed that reduction level of 100% B. germanica population could be achieved in five weeks treatment with initial population of cockroach before treatment ranging from 41 to 243. The result of this study showed that baiting formulation which consisted of banana-honey attractant with active ingredient of fipronil insecticide 0.03% was very effective to control B. germanica both in the laboratory and in the field.